2015
DOI: 10.1088/1742-5468/2015/11/p11002
|View full text |Cite
|
Sign up to set email alerts
|

Macrospin in external magnetic field: entropy production and fluctuation theorems

Abstract: We consider stochastic rotational dynamics of a macrospin at a constant temperature, in presence of an external magnetic field. Starting from the appropriate Langevin equation which contains multiplicative noise, we calculate entropy production (EP) along stochastic trajectories, and obtain fluctuation theorems. The system remains inherently out of equilibrium due to a spin torque supporting azimuthal current, leading to an excess EP apart from the EP due to heat dissipation. The anomaly may be removed using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…More in general, nowadays, statistical mechanics, thermodynamics, and rate theories play a crucial role in the description of several nanosystems and nanophysical phenomena, including folding and unfolding of two-state chains and macromolecules; [19][20][21][22][23] molecular motors; [24,25] muscle behavior; [26,27] adhesion, cohesion, and fracture processes; [28][29][30][31] friction and nanofriction; [32][33][34][35] micro-and nano-heat engines; [36][37][38] micromagnetism and spintronics; [39][40][41][42][43] as well as heat transfer in nanostructures, [44][45][46] just to name a few. The most widely used methodologies adopted to study these systems are based on the Langevin and Fokker-Planck equations.…”
Section: Doi: 101002/andp202300294mentioning
confidence: 99%
“…More in general, nowadays, statistical mechanics, thermodynamics, and rate theories play a crucial role in the description of several nanosystems and nanophysical phenomena, including folding and unfolding of two-state chains and macromolecules; [19][20][21][22][23] molecular motors; [24,25] muscle behavior; [26,27] adhesion, cohesion, and fracture processes; [28][29][30][31] friction and nanofriction; [32][33][34][35] micro-and nano-heat engines; [36][37][38] micromagnetism and spintronics; [39][40][41][42][43] as well as heat transfer in nanostructures, [44][45][46] just to name a few. The most widely used methodologies adopted to study these systems are based on the Langevin and Fokker-Planck equations.…”
Section: Doi: 101002/andp202300294mentioning
confidence: 99%
“…The excess EP is due to terms not appearing in stochastic energy balance. Recent studies on stochastic spin dynamics showed excess EP due to rotational motion that does not contribute to energetics [46,47]. It is clear from the discussions above that the definition of stochastic heat flux is directly derivable from the Langevin equation, and need not to explicitly refer to the time reversal parity of the dofs.…”
Section: Entropy and Dissipated Heatmentioning
confidence: 99%
“…Today, thermodynamic theories play a crucial role in the understanding of several nano-systems and physical phenomena, including macromolecular folding and unfolding [48][49][50], molecular motors [51,52], muscles behavior [53,54], adhesion processes [55][56][57], micro-and nano-heat engines [58][59][60], micromagnetism [61][62][63][64][65], and heat transfer in nanostructures [66][67][68], just to name a few.…”
Section: Introductionmentioning
confidence: 99%